Dampak Dugaan Gratifikasi Berindikasi Suap dalam Proses Initial Public Offering: Perlindungan Hukum Investor pada Kasus Lima Karyawan Bursa Efek Indonesia - salwa Salwa Dwiyanti Ruhiyat (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The capital market requires institutional integrity, information disclosure and legal certainty to enable investors to make rational investment decisions. Alleged bribery-indicated gratification in the Initial Public Offering (IPO) process involving five Indonesia Stock Exchange employees reveals legal risks in the assessment and listing of prospective issuers. This study examines two issues. First, the regulation of the IPO process for companies seeking to list shares on the Indonesia Stock Exchange. Second, the legal protection mechanisms for investors who may suffer losses due to violations in the IPO process. This study applies normative juridical research with statutory, conceptual and case approaches. The findings show that the Indonesian IPO legal framework regulates registration statements, prospectuses, share listing and capital market supervision. However, the case involving five IDX employees shows that investor protection cannot rely only on disclosure documents. Protection must cover the integrity of exchange personnel, internal supervision, audit trails of decisions, conflict-of-interest prohibitions, whistleblowing systems and administrative, civil and criminal enforcement. OJK and IDX must strengthen integrity-based supervision to keep the IPO process objective and maintain public confidence in the capital market.